Optimal source imaging in elastic media. Issue 2 (17th December 2015) - Bazargani, Farhad; Snieder, Roel
Abstract: Time-reversal modelling provides a simple and robust solution to source-imaging problems. However, for recovering a well-resolved image of the source, time-reversal requires a balanced illumination of the target from all angles. When acquisition is incomplete and a balanced illumination is not possible, the time-reversal solution may not be adequate. We present an inversion algorithm for computing the signals to be back propagated by an array of receivers with a given configuration in order to optimally image an unknown source in an elastic medium. This approach is based on minimizing the difference between the back-propagated wavefield and the time-reversed displacement field of the source in the near source region. The proposed method requires knowledge of the propagation medium and an estimate of the source location. Other information related to the source (e.g. source mechanism) is encoded within the data and not explicitly required by the method. The method is applicable in both elastic and acoustic media. We use synthetic examples to test the performance of our method, to analyse its sensitivities, potentials and limitations and to demonstrate its potential advantages over the time-reversal source-imaging technique.